Menakar Mutasi dan Kinerja Pegawai di Sektor Pendidikan - Amanda Yola Puspitasari; Dian Marlina Verawati (Jurnal Manajemen dan Bisnis, 2021)
This study aims to determine the description of employee mutations in the Department of Education and Culture of the City of Magelang. And to find out whether the mutation can improve employee performance or not. The research method used is quantitative and analyzed using descriptive qualitative methods. The sampling technique is Proportionate Stratified Random Sampling. The number of popylates in this study was 85 employees, while for the number of samples used were 8 employees with conditions including permanent employees and THL who had experienced mutations. Mutations held at the Department of Education and Culture of the City of Magelang in order to refresh the organization so it is not saturated. The results of this study indicate that the implementation of mutations has been done well by the leadership. This can be seen from the positive responses of employees who have mutations and high employee performance seen from the timeliness of employees in working and the use of working tools to the full.